Effects of centrally acting antihypertensive drugs on the microcirculation of spontaneously hypertensive rats - Estato,V. (2004)
We investigated the acute effects of centrally acting antihypertensive drugs on the microcirculation of pentobarbital-anesthetized spontaneously hypertensive rats (SHR). The effects of the sympatho-inhibitory agents clonidine and rilmenidine, known to activate both alpha2-adrenoceptors and nonadrenergic I1-imidazoline binding sites (I1BS) in the central nervous system, were compared to those of dicyclopropylmethyl-(4,5-dimethyl-4,5-dihydro-3H -pyrrol-2-yl)-amine hydrochloride (LNP 509), which selectively binds to the I1BS. Terminal mesenteric arterioles were observed by intravital microscopy. Activation of the central sympathetic system with L-glutamate (125 µg, ic) induced marked vasoconstriction of the mesenteric microcirculation (27 ± 3%; N = 6, P < 0.05). In contrast, the marked hypotensive and bradycardic effects elicited by intracisternal injection of clonidine (1 µg), rilmenidine (7 µg) and LNP 509 (60 µg) were accompanied by significant increases in arteriolar diameter (12 ± 1, 25 ± 10 and 21 ± 4%, respectively; N = 6, P < 0.05). The vasodilating effects of rilmenidine and LNP 509 were two-fold higher than those of clonidine, although they induced an identical hypotensive effect. Central sympathetic inhibition elicited by baclofen (1 µg, ic), a GABA B receptor agonist, also resulted in vasodilation of the SHR microvessels. The acute administration of clonidine, rilmenidine and LNP 509 also induced a significant decrease of cardiac output, whereas a decrease in systemic vascular resistance was observed only after rilmenidine and LNP 509. We conclude that the normalization of blood pressure in SHR induced by centrally acting antihypertensive agents is paralleled by important vasodilation of the mesenteric microcirculation. This effect is more pronounced with substances acting preferentially (rilmenidine) or exclusively (LNP 509) upon I1BS than with those presenting important alpha2-adrenergic activity (clonidine).